2022
DOI: 10.1186/s40001-022-00807-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective biomarkers for inflammation and infection are associated with post-operative complications following transperineal template prostate biopsy (TTPB): a single-centre observational clinical pilot-study

Abstract: Background Prostate cancer (PCa) and benign prostatic hyperplasia (BPH) are the most common prostate disorders in the UK, which cause considerable ill health in older men. Transperineal template prostate biopsy (TTPB) has emerged as a reliable procedure for the histopathological diagnosis of PCa and BPH due to its higher cancer detection rates. Although antiseptic preparation and antibiotic prophylaxis are used to ensure safety in patients undergoing surgical intervention, post-operative compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown that Th17 cells are considered an important group of cells that mediate in ammatory responses, and the release of interleukin-17A (IL-17A) by Th17 cells contributes to the maintenance of chronic in ammatory states and the development of a cancer-promoting microenvironment, which is closely related to the occurrence and development of PCa [10][11][12][13]. In addition, recent studies have indicated that interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) have different expressions in PCa tissues [14][15][16]. Another study found that interleukin-8 (IL-8) is also expressed in various cancers such as gastric cancer, esophageal cancer, and lung cancer to varying degrees [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that Th17 cells are considered an important group of cells that mediate in ammatory responses, and the release of interleukin-17A (IL-17A) by Th17 cells contributes to the maintenance of chronic in ammatory states and the development of a cancer-promoting microenvironment, which is closely related to the occurrence and development of PCa [10][11][12][13]. In addition, recent studies have indicated that interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) have different expressions in PCa tissues [14][15][16]. Another study found that interleukin-8 (IL-8) is also expressed in various cancers such as gastric cancer, esophageal cancer, and lung cancer to varying degrees [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that Th17 cells are considered an important group of cells that mediate inflammatory responses, and the release of interleukin-17A (IL-17A) by Th17 cells contributes to the maintenance of chronic inflammatory states and the development of a cancer-promoting microenvironment, which is closely related to the occurrence and development of PCa [10][11][12][13]. In addition, recent studies have indicated that interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) have different expressions in PCa tissues [14][15][16]. Another study found that interleukin-8 (IL-8) is also expressed in various cancers such as gastric cancer, esophageal cancer, and lung cancer to varying degrees [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%